Facile methods for generating human somatic cell gene knockouts using recombinant adeno-associated viruses - Kohli, Manu (Oxford University Press, 2004)
Emerging evidence suggests that recombinant adeno-associated viral (rAAV) vectors can be used for specific gene targeting in human somatic cells. We have developed an rAAV vector construction procedure employing fusion PCR and a single cloning step that considerably simplifies the knockout process. We demonstrate its utility by disrupting genes at specific positions within human colon cancer cells as well as within immortalized normal epithelial cells. This technology should be broadly applicable to in vitro studies that require the manipulation of the human genome.